The Likelihood of Financial Reporting Fraud: Does the Gender of CEO, CFO, Board of Commissioners, and Audit Committee Matter? - Intan Kurnida Julianti; Fuad Fuad (Universitas Katolik Soegijapranata Semarang, 2023)
The purpose of this study is to examine whether the presence of women in executive positions such as CEO, CFO, board of commissioners, and audit committee can reduce the occurrence of financial statement fraud. The sample was selected from manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2013 to 2022. The results of this study show that female CFOs and audit committees have a negative and significant influence. This indicates that the presence of women in the CFO position and the audit committee can reduce the occurrence of financial statement fraud in companies. This study offers a different perspective on the two-tier system of corporate governance in a developing country, namely Indonesia, about the impact of female CEO, CFO, board of commissioners, and audit committee on the occurrence of financial statement fraud. The practical implications of this research are first, the importance of promoting gender diversity of executives as a corporate governance mechanism. Second, it can provide recommendations or requirements for gender diversity as part of corporate governance mechanisms to create gender equality.